The Tragedy of Painless Needs - John D Loeser (Pain Research and Management)
Intractable pain demands the attention of both the patient and the physician. However, modern science and medicine cannot and should not promise the abolition of pain and suffering. The novel, Ingenious Pain, by Andrew Miller offers profound insights into the world of pain. Not all painful experiences in life are deleterious, nor should they all be prevented.